Causal Explanation of Academic Buoyancy Based on Teacher-Student Interaction, Academic and Hope Self-Efficacy - Ablolfazl Farid (Alzahra University, 2021)
The aim of this study was to investigate relationship between teacher-student interaction and academic buoyancy with the mediating role of academic self-efficacy and academic hope. This study is descriptive and study design is correlational plans type of the structural equations. Statistical population of the study formed all of second middle school students of Orumieh in 2019-2020 years of academic. Sampling was cluster random and 205 persons were selected as study sample. To collecting data was used of Murray and Zvoch teacher-student interaction scale (2011), Patrick, Hicks and Ryan’s academic self-efficacy scale (1997), Khormaie and Kamary academic hope scale (2017) and Hoseinchary and Dehganizade academic buoyancy scale (2012). Lisrel software was used to analyze the data and the proposed model was evaluated using structural equation modeling. The results of this study revealed that teacher-student interaction, academic self-efficacy and academic hope directly related to the academic buoyancy of students. So, the results of this study revealed that teacher-student interaction indirectly and through academic self-efficacy and academic hope related to the academic buoyancy of students. These findings of study support the mediating role of academic self-efficacy and academic hope in the model causal relationship between teacher-student interaction on academic buoyancy. Accordingly, it can be concluded that with the improvement of teacher-student interaction, Students' academic self-efficacy and academic hope increases and these factors together increases their academic buoyancy.